2021
DOI: 10.48550/arxiv.2106.10280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High star cluster formation efficiency in the strongly lensed Sunburst Lyman-continuum galaxy at z=2.37

E. Vanzella,
M. Castellano,
P. Bergamini
et al.

Abstract: We investigate the strongly lensed (µ ×10 − 100) Lyman continuum (LyC) galaxy, dubbed Sunburst, at z = 2.37, taking advantage of a new accurate model of the lens. A characterization of the intrinsic (delensed) properties of the system yields a size of 3 sq.kpc, a luminosity M UV = −20.3, and a stellar mass M 10 9 M ; 16% of the ultraviolet light is located in a 3 Myr old gravitationally-bound young massive star cluster (YMC) with an effective radius of ∼ 8 pc (corresponding to 1 milli-arcsec without lensing) a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 83 publications
6
27
0
Order By: Relevance
“…Three of those complexes show signatures of Wolf-Rayet stars, implying young ages of ∼ 5 Myr (Bastian et al 2006). Similar properties are observed in the Sunburst 5.1 knot presented in detail in Vanzella et al (2021a) and in some of our clumps shown in Figure D.1 of Vanzella et al (2021b). Other scenarios, such as the fragmentation of gas-rich discs, are potentially responsible for the observed high SFR among high redshift clumpy structures (Noguchi 1999;Dekel et al 2009).…”
Section: Radius -Sfr Relationsupporting
confidence: 74%
See 3 more Smart Citations
“…Three of those complexes show signatures of Wolf-Rayet stars, implying young ages of ∼ 5 Myr (Bastian et al 2006). Similar properties are observed in the Sunburst 5.1 knot presented in detail in Vanzella et al (2021a) and in some of our clumps shown in Figure D.1 of Vanzella et al (2021b). Other scenarios, such as the fragmentation of gas-rich discs, are potentially responsible for the observed high SFR among high redshift clumpy structures (Noguchi 1999;Dekel et al 2009).…”
Section: Radius -Sfr Relationsupporting
confidence: 74%
“…Indeed, recent observations of strongly lensed systems at 𝑧 ∼ 1 − 3 reveal the existence of clumps with sizes of ∼ 100 pc (Livermore et al 2012(Livermore et al , 2015Cava et al 2018), down to ∼ 10 pc (Rigby et al 2017) in some extremely magnified cases. Our previous studies (Vanzella et al 2017b(Vanzella et al , 2019(Vanzella et al , 2020(Vanzella et al , 2021aCalura et al 2021) have further extended this work to spectroscopically confirmed compact stellar structures, with sizes down to 10 pc, which are interpreted as young massive clusters and/or globular cluster precursors at 𝑧 ∼ 3 − 6 (see also Bouwens et al 2021). This demonstrates the importance of gravitational lensing to explore compact stellar structures considered as building blocks of high-redshift starforming galaxies.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…When EELGs are in the current burst phase, the massive stars are likely being formed in very young star clusters as demonstrated by spatially-resolved observations of a few strongly lensed galaxies at high redshift (e.g. Vanzella et al 2019Vanzella et al , 2021.…”
Section: Stellar Populations and Star Formation Histories Of The Most...mentioning
confidence: 99%